Relationship between positive emotion and learning motivation: The mediating role of resilience and the moderating role of social support - Teng, Yun; Qi, Fengjun; Liu, Xianhua (Edelweiss Applied Science and Technology, 2024)
College students exhibit a phenomenon of decreased academic motivation due to excessive use of mobile internet communication in interpersonal interactions. This study uses college students as a sample and collects data from 1,295 college students through an online questionnaire survey for empirical analysis. It explores the potential relationship between positive emotions and learning motivation and examines the mediating role of resilience and the moderating role of social support. The results show that: (1) Positive emotions have a significant positive impact on enhancing learning motivation and can effectively prevent the decline in learning motivation; (2) Resilience plays a partial mediating role between positive emotions and learning motivation, becoming an important factor in protecting learning motivation; (3) Social support has a moderating effect between positive emotions and learning motivation, playing a role in motivating learning motivation. Based on these results, the study provides valuable theoretical and practical insights for enhancing college students' resilience, improving social support, and cultivating positive emotions to prevent the decline in learning motivation.